Surface analysis of semiconductors and simulation using Python - Corray, Andre Mark (Nanyang Technological University, 2022)
Reflection High Energy Electron Diffraction (RHEED) is a real time in situ analysis technique for the characterisation of semiconductor surfaces. RHEED involves a beam of electrons, between 8 and 20KeV, incident upon the surface of a crystal substrate at a glancing angle. The electrons are diffracted and caught on a phosphor screen, where a diffraction pattern is formed. RHEED patterns are typically just a series of adjacent streaks or spots. The sample surface can be characterised by extracting the position and shape of the streaks. A charge-coupled device (CCD) camera captures the pattern, upon which, the pattern can be processed and analysed. This project uses the programming language, Python, to perform data analysis on the RHEED images. The program digitises the experimental images, stores pixel intensity data and utilises this data to extract the distance between streaks using a number of methods. By conducting analysis on the distance between streaks, information on the in-plane lattice constant of the sample can be obtained. Through monitoring the evolution of streak spacing for the experimental image patterns over time, information is provided on the variation of the in-plane lattice constant over growth time. Image processing methods were implemented to clarify the streaks. This eased the process of extracting the streak intensity profiles and pixels representing the streaks. This report discusses the development of the program step by step, the results, the issues encountered and proposed future work related to the project.